The transitional millisecond pulsar IGR J18245-2452 during its 2013 outburst at X-rays and soft gamma-rays - De Falco V; Kuiper L; Bozzo E; Ferrigno C; Poutanen J; Stella L; Falanga M (EDP SCIENCES S A, 2022)
IGR J18245-2452/PSR J1824-2452I is one of the rare transitional accreting millisecond X-ray pulsars, showing direct evidence of switches between states of rotation-powered radio pulsations and accretion-powered X-ray pulsations, dubbed transitional pulsars. IGR J18245-2452 with a spin frequency of similar to 254.3 Hz is the only transitional pulsar so far to have shown a full accretion episode, reaching an X-ray luminosity of similar to 10(37) erg s(-1) permitting its discovery with INTEGRAL in 2013. In this paper, we report on a detailed analysis of the data collected with the IBIS/ISGRI and the two JEM-X monitors on-board INTEGRAL at the time of the 2013 outburst. We make use of some complementary data obtained with the instruments on-board XMM-Newton and Swift in order to perform the averaged broad-band spectral analysis of the source in the energy range 0.4-250 keV. We have found that this spectrum is the hardest among the accreting millisecond X-ray pulsars. We improved the ephemeris, now valid across its full outburst, and report the detection of pulsed emission up to similar to 60 keV in both the ISGRI(10.9 similar to) and Fermi/GBM (5.9 sigma) bandpass. The alignment of the ISGRI and Fermi GBM 20-60 keV pulse profiles are consistent at a similar to 25 mu s level. We compared the pulse profiles obtained at soft X-rays with XMM-Newton with the soft gamma-ray ones, and derived the pulsed fractions of the fundamental and first harmonic, as well as the time lag of the fundamental harmonic, up to 150 mu s, as a function of energy. We report on a thermonuclear X-ray burst detected with INTEGRAL, and using the properties of the previously type-I X-ray burst, we show that all these events are powered primarily by helium ignited at a depth of y(ign) similar to 2.7 x 10(8) g cm(-2). For such a helium burst the estimated recurrence time of Delta t(rec) similar to 5.6 d is in agreement with the observations.